Pengaruh Dana Ekonomi Bergulir Proyek Penanggulangan Kemiskinan di Perkotaan (P2KP) Terhadap Peningkatan Pemberdayaan Masyarakat: Kabupaten Lumajang - Ninik Lukiana; Hesti Budiwati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2011)
Urban Poverty Project (P2KP) one answer to the problems of poverty in urban areas, through P2KP government provides financial assistance to implement the process of community empowerment and continuous learning. One type of economic activity from P2KP is rolling, that is allocated funds for lending activities to the poor in order to form a new business or expand an existing business, with its implementation involving the relevant communities. The purpose of this study is, to determine the influence of economic funds rolling P2KP to increased community empowerment Lumajang, to find strengths and weaknesses of the implementation of economic revolving fund in Lumajang P2KP. To answer this research purpose, then there are some indicators that the number of SHGs and SHG members, the value of revolving loans disbursed, the health management of revolving loans, development revolving loan coverage to low-income communities, the status of the audit by an independent auditing agency. The result is 4 (four) indicator shows the success and significant impact on increasing community empowerment, while indicators of health levels are still less than satisfactory. But overall economy revolving fund in Lumajang P2KP show success in increasing community empowerment. In addition to these successes there are some weaknesses, especially regarding the ability of human resources.